2021
DOI: 10.3390/healthcare9111413
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Effectiveness of Long-Term Care Following Integrated Discharge Planning: A Prospective Cohort Study

Abstract: Little is known about the effects of seamless hospital discharge planning on long-term care (LTC) costs and effectiveness. This study evaluates the cost and effectiveness of the recently implemented policy from hospital to LTC between patients discharged under seamless transition and standard transition. A total of 49 elderly patients in the standard transition cohort and 119 in the seamless transition cohort were recruited from November 2016 to February 2018. Data collected from medical records included the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…27 Similarly, another study revealed that interdisciplinary approach improved the quality of care during transition from hospital-based to home-based care. 28 However, health workers in this study reported a lack of a multidisciplinary approach to discharge planning. We found out that the decision to discharge a patient was made by a senior doctor (physician) only.…”
Section: Dovepressmentioning
confidence: 74%
“…27 Similarly, another study revealed that interdisciplinary approach improved the quality of care during transition from hospital-based to home-based care. 28 However, health workers in this study reported a lack of a multidisciplinary approach to discharge planning. We found out that the decision to discharge a patient was made by a senior doctor (physician) only.…”
Section: Dovepressmentioning
confidence: 74%
“…Alongside these training needs, the importance of continuity of care was identified by service users and healthcare workers. Ensuring that, where possible, the patient sees the same healthcare worker, not only reduces costs ( Wang et al 2021 ) but improves patient outcomes ( Pereira Gray et al, 2018 ).…”
Section: Commentarymentioning
confidence: 99%